Effect of Divergent Feeding Regimes During Early Life on the Rumen Microbiota in Calves - Cristobal-Carballo, Omar; McCoard, Sue A.; Cookson, Adrian L.; Laven, Richard A.; Ganesh, Siva; Lewis, Sarah J.; Muetzel, Stefan (Frontiers in Microbiology, 2021)
The objective of this study was to determine whether divergent feeding regimes during the first 41 weeks of a calf’s life, are associated with long-term changes in the rumen microbiota, and the associated fermentation end-products. Twenty-four calves (9±5d of age) were arranged in a 2x2 factorial design with two divergent treatments across 3 dietary phases. In phase 1 (P01), calves were offered a low-milk volume/concentrate starter diet with early weaning (CO) or high-milk volume/pasture diet and late weaning (FO). In phase 2 (P02), calves from both groups were randomly allocated to either high-quality (HQ) or low-quality (LQ) pasture grazing groups. In phase 3 (P03), calves were randomly allocated to one of two grazing groups and offered the same pasture-only diet. During each dietary phase, methane (CH4) and hydrogen (H2) emissions, and dry matter intake (DMI) were measured in respiration chambers and rumen samples for evaluation of microbiota and short-chain fatty acids (SCFA) characterizations were collected. In P01, CO calves had a higher solid feed intake but a lower CH4 yield (yCH4) and acetate:propionate ratio (A:P) compared to FO calves. The ruminal bacterial community had lower proportions of cellulolytic bacteria in CO than FO calves. The archaeal community was dominated by Methanobrevibacter boviskoreani in CO calves and by Mbb. gottschalkii in FO calves. These differences however did not persist into P02. Calves offered HQ pastures had greater DMI and lower A:P ratio than calves offered LQ pastures, but yCH4 was similar between groups. The cellulolytic bacteria had lower proportions in HQ than LQ calves. In all groups, the archaeal community was dominated by Mbb. gottschalkii. No treatment interactions were observed in P02. In P03, all calves had similar DMI, CH4 and H2 emissions, SCFA proportions and microbial compositions and no interactions with previous treatments were observed. These results indicate that the rumen microbiota and associated fermentation end-products are driven by the diet consumed at the time of sampling, and that previous dietary interventions do not lead to a detectable long-term microbial imprint or changes in rumen function.